Effective Coaching, and the Fallacy of Sustainable Change - Kohli, Arun (Management for Professionals, 2016)
This book presents an evidence-based discussion of two critical areas that are gaining importance in the business world and personal development alike: namely, coaching and being a coach. Does coaching work? If so, then for whom does it add value and what is it really all about? Today, just about everybody in personal services seems to have become a coach. Is it just another modern expression or a buzzword for something that other disciplines were already providing? This book seeks to arrive at clear answers to these questions, providing a thought-provoking and insightful narrative that is likely to leave behind a lasting impact on the industry and its potential clients.